Pembinaan Khusus Narapidana Lanjut Usia di Lembaga Pemasyarakatan Kelas 1 Surabaya - Cindhy Atika Rahmawati; Eko Wahyudi (Pusat Riset dan Inovasi Nasional, 2023)
Elderly prisoners are classified as a special vulnerable group because at that age they have decreased immunity and physical weakness so special treatment is needed. Correctional Institution must be able to fulfill the rights of elderly prisoners while they are serving their sentences. The purpose of this research is to find out the implementation of guidance for elderly prisoners and the obstacles faced by the Surabaya Class 1 Correctional Institution. The type of this study is empirical legal research. The results showed that the guidance for elderly prisoners at the Surabaya Class 1 Correctional Institution has not been running optimally.. This is due to budget constraints from the government, lack of human resources, insufficient infrastructure, the covid-19 pandemic, lack of support from the families of prisoners, and the difficulties of marketing the work products of prisoners. But with these obstacles, various kinds of efforts can be made to handle the problem